Agatha Christie's Poirot. The mysterious affair at Styles [videorecording (DVD)] - Fraser, Hugh; Suchet, David; Jackson, Philip, 1948-; Moran, Pauline; Christie, Agatha, 1890-1976 (Granada Media International ; distributed exclusively by Acorn Media, 2000)
Set in the summer of 1917, the story follows the war-wounded Captain Arthur Hastings to the Styles St. Mary estate of his friend John Cavendish. The Cavendish household is wrought with tension due to the marriage of John's widowed mother to a suspicious younger man. Hastings runs into his old friend Hercule Poirot In the village. When the estate's trouble turns deadly, the friends unite to solve a most baffling case.